Surgical Retrieval of an Intraocular Needle Following Intravitreal Bevacizumab Injection. (July 2019) - Mathai, Mariam; Levinson, Joshua D.; Khanifar, Aziz A.; Smithen, Lindsay M.
Purpose: The purpose of this case report is to describe a case of iatrogenic intraocular foreign body due to a fractured 30-gauge needle following intravitreal injection of bevacizumab. Methods: A case report is presented. Results: The patient presented with a 30-gauge needle in the vitreous cavity after receiving an intravitreal injection of bevacizumab for diabetic macular edema. Bilateral eye shields were placed to reduce movement of the foreign body and decrease the risk of injury to the lens or retina. The needle was successfully removed via a combination of 23-gauge pars plana vitrectomy and removal of the foreign body via a transscleral approach through the initial injection site. Visual acuity improved to 20/25 2 months after surgery. Conclusions: We present the successful preoperative management and surgical removal of a needle fragment from the vitreous cavity after the needle fractured during intravitreal injection.